Case Report: Drug-Induced Immune Haemolytic Anaemia Caused by Cefoperazone-Tazobactam/ Sulbactam Combination Therapy - Wu, Yuanjun; Wu, Yong; Ji, Yanli; Liang, Jiajie; He, Ziyi; Liu, Yanhui; Tang, Li; Guo, Ganping (Frontiers in Medicine, 2021)
There has previously been a report of a patient developing haemolytic anaemia following exposure to cefoperazone. Another case has been reported involving the detection of cefoperazone-dependent antibodies in the absence of immune haemolytic anaemia. To date, no serological evidence has been reported to suggest that cefoperazone can lead to drug-induced immune haemolytic anaemia (DIIHA). This report aims to fill these gaps in knowledge by describing a case of DIIHA caused by cefoperazone-dependent antibodies. A 59-year-old man developed fatal haemolytic anaemia while receiving cefoperazone-tazobactam or cefoperazone-sulbactam for the treatment of a lung infection that occurred after craniocerebral surgery. This eventually led to renal function impairment. Prior to the discontinuation of cefoperazone treatment, the patient showed strong positive (4+) results for both anti-IgG and anti-C3d direct antiglobulin test (DAT), while cefoperazone-dependent IgM and IgG antibodies were detected. The patient’s plasma and O-type RBCs were incubated with tazobactam or sulbactam solution at 37ºC for 3 h, the results of DAT for anti-IgG and anti-C3d were both positive. Forty-three days after the discontinuation of cefoperazone, the results of DAT for anti-IgG and anti-C3d were negative. Meanwhile incubation of the patient’s fresh serum and his own RBCs with cefoperazone at 37ºC, gave rise to mild haemolysis, and the results of DAT for both anti-IgG and anti-C3d were positive. It is suggested that cefoperazone-dependent antibodies can activate complement, and the non-immunologic protein adsorption effect of tazobactam or sulbactam can enhance IgG and complement binding to RBCs. This may promote the formation of immunocomplexes and complement activation, thereby aggravating haemolysis.